4
$\begingroup$

Let $P$ and $Q$ be functions of $r$ and $r$ be a function of $(x,y,z)$. Also let $f$ be a function of $(x,y)$.

If: $$P(x,y,z) + f (x,y)= Q(x,y,z) \tag{1} $$ By $(1)$ $$\dfrac{\partial P}{\partial x} \neq \dfrac{\partial Q}{\partial x} \Rightarrow \dfrac{dP}{dr} \dfrac{\partial r}{\partial x} \neq \dfrac{dQ}{dr} \dfrac{\partial r}{\partial x}\Rightarrow \dfrac{dP}{dr} \neq \dfrac{dQ}{dr} \tag{2} $$ Also by $(1)$ $$\dfrac{\partial P}{\partial z} = \dfrac{\partial Q}{\partial z}\Rightarrow \dfrac{dP}{dr} \dfrac{\partial r}{\partial z} = \dfrac{dQ}{dr} \dfrac{\partial r}{\partial z} \Rightarrow \dfrac{dP}{dr} = \dfrac{dQ}{dr} \tag{3}$$

$(2)$ and $(3)$ contradict. Why is this so?

$\endgroup$
  • $\begingroup$ The formula (1) seems wrong, missing an the "r" cc @Robert $\endgroup$ – quid Mar 3 '18 at 12:46
  • $\begingroup$ If (1) is true in the sense that $P$ and $Q$ are functions of $r$, then what does that say about $f(x,y)$? Or else, what does that say about $r$? Or $P$ and $Q$? $\endgroup$ – Zorawar Mar 3 '18 at 17:01
4
$\begingroup$

You say that: $\qquad P(r(x,y,z))+f(x,y)=Q(r(x,y,z))$

Which is to say: $\quad f(x,y)=[Q-P]\circ r(x,y,z)$

Therefore $\qquad\quad~~ 0~{= \dfrac{\partial f(x,y)}{\partial z}\\=\left[\dfrac{\mathsf d [Q-P](r)}{\mathsf dr\qquad\qquad}\right]\!\!(x,y,z)\cdot\dfrac{\partial r(x,y,z)}{\partial z\qquad\quad}}$

So either $\dfrac{\mathsf d [Q-P](r)}{\mathsf dr\qquad\qquad}=0$ or $\dfrac{\partial r(x,y,z)}{\partial z\qquad\quad} =0$

In the first case, $f(x,y)$ must be a constant, and in the second $r$ is invariant with respect to $z$.   In either case, there is no contradiction involved.

If $f(x,y)$ is constant, then $\dfrac{\partial P}{\partial x}+0=\dfrac{\partial Q}{\partial x}$.

If $\dfrac{\partial r(x,y,z)}{\partial z\qquad\quad}=0$ then $\dfrac{\partial P}{\partial z}=\dfrac{\partial Q}{\partial z}=0$.

$\endgroup$
4
$\begingroup$

If $$P(r(x,y,z)) + f(x,y)= Q(r(x,y,z)) \tag{1}$$ then $$\dfrac{d P(r)}{d r}\dfrac{\partial r}{\partial x}+\dfrac{\partial f}{\partial x}=\dfrac{d Q(r)}{d r}\dfrac{\partial r}{\partial x} \tag{2}$$ and $$\dfrac{d P(r)}{d r}\dfrac{\partial r}{\partial z}=\dfrac{d Q(r)}{d r}\dfrac{\partial r}{\partial z} \tag{3}.$$ In my opinion (2) does not contradict (3): if $\dfrac{\partial r}{\partial z}\not=0$ then, from (3), $\dfrac{d P(r)}{d r}=\dfrac{d Q(r)}{d r}$ and, by (2), it follows that $\dfrac{\partial f}{\partial x}=0$. In the same way $\dfrac{\partial f}{\partial y}=0$. The difference $P(r)-Q(r)=f$ could be identically constant.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.